The level of customer satisfaction on service quality of Mazda service centre at Glenmarie / Siti Salwa Halim - Halim, Siti Salwa (2015)
This research aims to investigate the level of customer satisfaction on service quality of Mazda Service Centre at Glenmarie by using SERVQUAL analysis. It is also aims to determine which of the five (5) dimension of SERVQUAL has the most influence on the level of customer satisfaction. The five dimensions of SERVQUAL, which are tangibles, reliability, responsiveness, assurance, and empathy, are the identified independent variables, while customer satisfaction as the identified dependent variable. Each of the dimensions of SERVQUAL was tested to determine and measure the relationship with the level of customer satisfaction. Besides that, this study also suggests the recommendation based on the most important factor that influencing customer satisfaction at Mazda Service Centre at Glenmarie. Mazda can emphasize on that factor to improve their service quality. The questionnaires are filled by the customers who already purchase Mazda cars and engaging the service at Mazda Service Centre at Glenmarie. A total of 100 respondents participated in the survey. The participating respondents represented a return rate of 100% after distribute the questionnaire directly to the respondents.